Reasons of Requests for Psychological Help in an Emergency Hospital - A.A. Rakhmanina; A.S. Gamzatova; M.D. Tseitlina; A.V. Koroleva (Клиническая и специальная психология)
Psychological assistance to patients in an emergency multidisciplinary hospital is increasingly relevant due to the influence of mental disorders and emotional maladjustment on treatment, the patient’s internal perception of their illness, and adherence to treatment. Since hospitalization is inherently a stressful factor that can contribute to the development of anxiety and depressive symptoms, psychological support for patients and often their loved ones is an integral part of the treatment process. However, studies on the emotional state of patients at the time of hospitalization are limited and primarily focus on assessing the level of current stress. Patients admitted to the hospital often experience symptoms of emotional maladjustment long before hospitalization, which can significantly impact their adaptation to the hospital environment and the treatment process as a whole. This article analyzes the reasons for seeking psychological help during hospitalization in an emergency hospital and examines the relationship between these reasons and the level of emotional maladjustment. The analysis of primary issues was conducted by coding each case according to the most prominent problem presented. A total of 379 consultations were analyzed, identifying problems associated with psychological distress. The sample consisted of 122 men and 257 women, with an average age of 50 years. Also, some patients completed the Hospital Anxiety and Depression Scale (HADS), including 30 men and 50 women. The results of the study showed that one of the most common reasons for seeking psychological help was related to situational reactions to stress. However, the majority of patients in this group did not have elevated scores on the Hospital Anxiety and Depression Scale. In addition, a significant percentage (37% of all consultations) of patients were referred for psychological consultation due to emotional problems that had been present before hospitalization. Notably, patients in this group were most often among those with clinically significant levels of anxiety and depression. The data obtained may indicate that the main reason for the deterioration of the emotional state at the time of hospitalization is not hospitalization itself, but problems that the patient has encountered outside the hospital walls.